Assessing the Role of Carotenoid Cleavage Dioxygenase 4 Homoeologs in Carotenoid Accumulation and Plant Growth in Tetraploid Wheat - Yu, Shu; Tian, Li (Frontiers in Nutrition, 2021)
The dietary needs of humans for provitamin A carotenoids arise from their inability to synthesize vitamin A de novo. To improve the status of this essential micronutrient, special attention has been given to biofortification of staple foods, such as wheat grains, which are consumed in large quantities but contain low levels of provitamin A carotenoids. However, there remains an unclear contribution of metabolic genes and homoeologs to the turnover of carotenoids in wheat grains. To better understand carotenoid catabolism in tetraploid wheat, Targeting Induced Local Lesions in Genomes (TILLING) mutants of CCD4, encoding a Carotenoid Cleavage Dioxygenase (CCD) that cleaves carotenoids into smaller apocarotenoid molecules, were isolated and characterized. Our analysis showed that ccd4 mutations co-segregated with Poltergeist-like (pll) mutations in the TILLING mutants of A and B subgenomes, hence the ccd-A4 pll-A, ccd-B4 pll-B, and ccd-A4 ccd-B4 pll-A pll-B mutants were analyzed in this study. Carotenoid profiles are comparable in mature grains of the mutant and control plants, indicating that CCD4 homoeologs do not have a major impact on carotenoid accumulation in grains. However, the neoxanthin content was increased in leaves of ccd-A4 ccd-B4 pll-A pll-B relative to the control. In addition, four unidentified carotenoids showed a unique presence in leaves of ccd-A4 ccd-B4 pll-A pll-B plants. These results suggested that CCD4 homoeologs may contribute to the turnover of neoxanthin and the unidentified carotenoids in leaves. Interestingly, abnormal spike, grain, and seminal root phenotypes were also observed for ccd-A4 pll-A, ccd-B4 pll-B, and ccd-A4 ccd-B4 pll-A pll-B plants, suggesting that CCD4 and/or PLL homoeologs could function towards these traits. Overall, this study not only reveals the role of CCD4 in cleavage of carotenoids in leaves and grains, but also uncovers several critical growth traits that are controlled by CCD4, PLL, or the CCD4-PLL interaction.